In vitro study on the biotransformation and cytotoxicity of three hexabromocyclododecane diastereoisomers in liver cells. (October 2016) - Huang, Xiaomei; Chen, Cen; Shang, Yu; Zhong, Yufang; Ren, Guofa; Yu, Zhiqiang; An, Jing
Abstract: In order to clarify the cytotoxicity of hexabromocyclododecane (HBCD) diastereoisomers, and to investigate the correlation of cytotoxicity and biotransformation of HBCDs, the immortalized human liver cells L02 and human hepatoma cells HepG2 were exposed to individual HBCD diastereoisomer (α-, β- and γ-HBCD). Cytotoxicity was assayed in terms of cell viability, reactive oxygen species (ROS) level and DNA damage. Metabolic rate, bioisomerization and enantiomer fractions were analyzed using the liquid chromatograph coupled to triple quadrupole mass spectrometer (LC-MS/MS). The α-, β- and γ-HBCD all had cytotoxicity in L02 and HepG2 cells with the toxicity order β-HBCD ≥ γ-HBCD > α-HBCD according to the results of proliferation assay. The cytotoxicity mechanism between the two cells seemed different: a) the stability of intracellular redox state plays an important role in inducing cell toxicity in HepG2 cells. b) DNA damage status is central to inhibit proliferation in L02 cells. The metabolic capability of HepG2 was superior to L02 for HBCD diastereoisomers, which may explain the greater toxicity of HBCDs in HepG2 cells. The bioisomerization and enantiomer enrichment were also detected in this study, although the results were inconsistent with other reports, which might result from species-specific differences in HBCDs metabolism or experimental conditions. The cytotoxicity and metabolic mechanism of individual enantiomers must be further investigated to evaluate the health risks of HBCDs. Highlights: The cytotoxicity range of three HBCD diastereoisomers was β-HBCD ≥ γ-HBCD > α-HBCD. The stability of intracellular redox plays an important role in inducing cell toxicity in HepG2 cells. DNA damage status plays leading role to inhibit cell proliferation in L02 cells. The degradation rate of HBCD diastereoisomers influenced their toxicity effect.